Triptycene-based self-assembled monolayer as a template for successive click reactions - Das, Saunak; Ishiwari, Fumitaka; Shoji, Yoshiaki; Fukushima, Takanori; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2023)
Triptycene-based molecules represent a promising platform for tripodal monomolecular assembly on solid substrates. The versatility of the approach can be increased significantly if a decoration of the assembled tripods by purpose-specific functional groups will be possible. In this context, the possibility of click reaction between the 10-ethynyl-substituted 1,8,13-trimercaptomethyltriptycene monolayer (EtTripS) on Au(111) and an azide-decorated substituent is tested and additionally verified by a subsequent derivatization reaction. The primary monolayer is shown to exhibit dense molecular packing, tripodal adsorption geometry, and high orientational order, which qualify it well as a template for subsequent reactions. The characteristic spectroscopic fingerprints of the click and derivatization reactions were recorded. The overall impact of these reactions on the work function of the EtTripS-engineered substrate─used as a measure of their efficiency and as an example of functional properties─was well comparable with the effect of the analogous substitution (−CF3) for monodentate monolayers, emphasizing the high potential of the on-surface modification approach.